Análise da coleta de resíduos de equipamentos elétricos e eletrônicos nos ecopontos de Belo Horizonte, MG - Débora Ferreira dos Santos (2018)
In the management of Waste Electrical and Electronic Equipment (WEEE), the collection stage is determinant for good performance of later stages. An efficient collection can enable reverse logistics, promoting reduction of natural resources extraction from environment and reduction of occupied areas in sanitary landfills. Above all, it can provide the insertion of social actors involved through recycling with a potential for income generation, the priority point of Law 12.305 (2010), which deals with the National Solid Waste Policy (NSWP). This research is a case that aims to evaluate the collection activities of WEEE in Belo Horizonte (MG), Brazil. The field data collection was carried out in 2015 and the bibliographic and documentary research was extended until 2018, bringing an updated review on the management of WEEE. 217 sites with potential for WEEE collection were surveyed, resulting in a physical inventory of 96 ecopoints that received some type of WEEE, representing 44% of the total visited sites. There were intense informal activities related to the management of WEEE. The lack of information and knowledge, made it hard to identify the waste streams and made it impossible to evaluate the collection performance. The triangulation of the obtained data in the field and the data from available literature, although scarce, allowed to identify the elements that interfere in collect performance. Until the sector agreement between the actors responsible for reverse logistics is signed, there is no more severe application of NSWP. Most of the existing ecopoints belong to the private sector, which specializes in dismantling and recycling of green line materials (computers, computer accessories tablets, cell phones and batteries) and the brown line (TVs and monitors) that have some commercial value. However, materials of lower commercial value such as white line (refrigerators, stoves and etc.) and blue line (drill, iron, etc.) are received at the public units by means of voluntary home delivery and are sent to the sanitary landfill. The public authority does not recognize the responsibility for the disposal of WEEE and officially does not receive such waste. The collection of WEEE in Belo Horizonte still very incipient and, in practice, it is not yet in the strategic priority of the municipality strategy as verified in its Municipal Integrated Solid Waste Management Plan, prepared in 2017